Security Analysis of Smart Grids. (10th June 2022) - Ibrahim, Mariam; Elhafiz, Ruba
Abstract : An attack graph is a beneficial tool to network defenders, demonstrating the routes that an attacker can utilize to acquire entry to a target network. Cyber-attacks endanger the security of smart grids as a result of the presence of vulnerabilities in the diversified structural units establishing it. This paper introduces a new tool built using Python language and Jupyter Notebook to enumerate an attack graph for a smart grid. The smart grid is formally presented and implemented, determining system design, links, weaknesses, resources, potential attack instances, and their pre- and post-conditions. The tool is utilized to automatically determine an attack sequence in the form of a counterexample. It constructs the counterexamples, encodes those for requirement loosening, and iterates up until all attack sequences are disclosed. Then, the attack graph causing disruption of the smart grid's workflow is graphically visualized.